Investigation of Dy3+ Ion Doped Borate Glasses and Their Potential for WLED and Laser Application - Juniastel Rajagukguk; Lia Yuliantini; Fitrilawati Fitrilawati; Mitra Djamal; Jakrapong Kaewkhao (Journal of Engineering and Technological Sciences, 2020)
In this research, Dy3+ ion-doped Na2O-PbO-ZnO-Li2O-B2O3 glasses were developed using the melt and quenching method. The addition of Dy3+ ions in the glass improved the optical properties. The XRD graph verified the amorphous of the glass sample. FTIR showed the vibration of BO3 and BO4 in the structure of the glass. The enhancement of NBOs in the structure of the glass affected the reduction of the bandgap energy of the glass. The hypersensitive transition of the present glass was found at 1270 nm (infrared region) due to electron movement from the 6H15/2 level to the 6H9/2+6F11/2 level. The strong white emission of the glasses came from 575 nm (yellow region) and 483 nm (blue region) when excited by 349 nm. The CIE 1931 chromaticity was located at (0.37;0.40) and verified the white emission of the glasses. Meanwhile, the trendline of the JO parameter was W2 > W6 > W4,indicating the high ionic character of the glass structure. The value of the calculated branching ratio and emission cross-section of Dy_1.0 glass was 0.64 and 0.90 x 10-20 cm2, respectively. From the analysis of results, the present glass has high potential for WLED and laser application.